An unsuspected and unrecognized cause of medication overuse headache in a chronic migraineur—essential oil-related medication overuse headache: A case report. (8th January 2020) - Mathew, Thomas; John, Saji K
Essential oils are widely used by people for common ailments like headache and backache. We report a case of chronic daily headache in an adolescent migraineur refractory to most antimigraine drugs secondary to topical application of essential oils containing camphor and eucalyptus. A 14-year-old boy presented with chronic daily headache of 1-year duration, refractory to four antimigraine drugs including valproate and topiramate. He was daily applying a balm called Amruthanjan (10% camphor and 14.5% eucalyptus) on his forehead to relieve headache. Patient had complete relief of headache in 2 weeks after stopping the balm application. All his antimigraine drugs were tapered and stopped over a period of 3 months. At 1-year follow-up, he is headache free. Brain-stimulant essential oils of camphor and eucalyptus may be an important unrecognized cause of medication overuse headache.